Associative transcriptomics study dissects the genetic architecture of seedling biomass‐related traits in rapeseed (Brassica napus L.). (7th February 2021) - Xu, Jinsong; Zhan, Hui; Xie, Yanping; Tian, Gang; Xie, Lingli; Xu, Benbo; Zhao, Yongguo; Lu, Guangyuan; Zhang, Xuekun
Abstract: It was observed that the seedling biomass was correlated with final seed yield in many crops. It is helpful to dissect the genetic architecture of seedling biomass‐related traits for high yield breeding of rapeseed ( Brassica napus L.). To date, the genetic architecture of seedling biomass‐related traits is still unclear in B. napus . To identify candidate genes associated with high seedling biomass, a genome‐wide association study of seedling biomass‐related traits under normal growth condition and waterlogging stress was conducted with 156 B. napus accessions. We detected six peaks including 55 single‐nucleotide polymorphisms (SNPs) significantly associated with the above‐mentioned traits in SNP association analysis and 142 UniGenes showed significantly associated with traits in gene expression marker (GEM) association analysis. Candidate genes located within the linkage disequilibrium (LD) blocks were identified, such as ADP GLUCOSE PYROPHOSPHORYLASE LARGE SUBUNIT 1 ( BnaC2APL1 ), PS II OXYGEN‐EVOLVING COMPLEX 1 ( BnaC9PSBO1 ), their ortholog in the Arabidopsis thaliana has been shown to play key roles in starch biosynthesis and photosynthesis. Resequencing of genomic regions revealed the non‐synonymous SNPs in coding regions may be the functional polymorphisms in the two candidate genes. Our results provide insight into the molecular mechanisms underlying the establishment of high‐seedling biomass B. napus and lay a foundation for the characterization of candidate genes aimed at developing high‐seedling B. napus varieties.